Model selection for ecologists: the worldviews of AIC and BIC - Aho, Ken; Derryberry, DeWayne; Peterson, Teri (Ecology (Durham), 2014)
Ecologists frequently ask questions that are best addressed with a model comparison approach. Under this system, the merit of several models is considered without necessarily requiring that (1) models are nested, (2) one of the models is true, and (3) only current data be used. This is in marked contrast to the pragmatic blend of Neyman-Pearson and Fisherian significance testing conventionally emphasized in biometric texts (Christensen 2005), in which (1) just two hypotheses are under consideration, representing a pairwise comparison of models, (2) one of the models, H sub(0), is assumed to be true, and (3) a single data set is used to quantify evidence concerning H sub(0).